Executive Support System For Business and Employee Performance: Analysis Of The Ease of Use Of Information System, User Satisfaction and Quality of Information System - Parulian, Ronald; Ali, Hapzi; Nyoman Sawitri, Ni (Greenation Publisher & Yayasan Global Research National, 2023)
Abstract: This article aims to examine the relationship between various variables in order to identify potential solutions. The research method used is qualitative, involving the analysis of published journals. Out of the five factors reviewed, three are independent variables, namely the ease of use of information systems, information system user satisfaction, and quality of information system. The executive support system for business is considered the intervening variable, while employee performance is the dependent variable. The analysis of twenty published journals concludes that the independent variables have a positive and significant impact on employee performance. The literature review suggests that businesses should take all factors into account to improve employee performance. Keywords: Ease of Use of Information System, User Satisfaction, quality of information system, Executive Support System for Business, Employee Performance